THE EFFECT OF WORK ETHOS ON THE TEACHERS PERFORMANCE OF SMP ST. IGNASIUS MEDAN - Paian Tamba; Aman Simaremare (Quaerite Veritatem : Jurnal Pendidikan, 2023)
The purpose of this study was to determine the effect of work ethic on teacher performance at St. Junior High School. Ignatius Medan. The type of research used in this research is quantitative research. The population in this study were all teachers and employees at SMP St. Ignasius Medan numbered 32 people. The sampling technique in this study used the saturated sample method where all members of the population were used as samples. Based on the results of research and data processing conducted by researchers, it can be concluded that work ethic has a significant influence on teacher performance at SMP St. Ignatius Medan